FAKTOR YANG MEMPENGARUHI PARTISIPASI MASYARAKAT DALAM PENCEGAHAN COVID-19 DI KELURAHAN PASAR GUNUNGTUA KABUPATEN PADANG LAWAS UTARA - Siregar, Siti Arafah; Siagian, Mindo Tua; Sitorus, Mido Ester J.; Richadi, R. Kintoko; Pardede, Jek Amidos; Hakim, Lukman (Universitas Pahlawan, 2022)
Covid-19 is an infectious disease caused by a new type of coronavirus with common symptoms of fever, fatigue, cough, convulsions and diarrhea. 8 Covid-19 cases were found and 1 person died in Pasar Gunungtua Village. It is suspected that this is due to the low participation of the community in preventing Covid-19. The purpose of the study was to analyze the factors that influence community participation in preventing Covid-19 in Pasar Gunungtua Village, North Padang Lawas Regency. The type of research is descriptive analytic with a cross sectional approach carried out in March-June 2021. The population is the head of the family who lives in Pasar Gunungtua Village as many as 2,507 families and the sample is 113 people. The results of the bivariate analysis showed that all independent variables had an effect on community participation in the prevention of Covid-19 (p<0.05). Based on the results of multivariate analysis, the dominant variables that influence community participation in preventing Covid-19 are opportunity (OR=5,10), willingness (OR=10,810), ability (OR=6,791), the role of the environmental head (OR=6,613) and the role of cadres/health workers (OR=3.765). It was concluded that people who have a good will tend to participate 10,810 times in preventing COVID-19 disease than those who have a bad will.